DENITRIFIKASI LIMBAH NITRAT PADA BERBAGAI TINGKAT KEASAMAN DENGAN MEMANFAATKAN MIKROBA AUTOTROPH - Nugroho, Rudi (Jurnal Air Indonesia, 2005)
A biological denitrification using autotrophic bacteria in batch suspension runs was investigated to clarify the effect of pH on denitrification rate. Elemental sulfur was employed as an electron donor. The culture of autotrophic bacteria was obtained from activated sludge by acclimatization. The effect of pH on denitrification rate could be expressed by bell-shape equation with optimum pH of 7,07. However at a pH range of 5,5 to 8,0, the denitrification rate significantly fastl. Therefore, the application of the denitrification of wastewater using autotrophic bacteria is suggested running well although without controlling pH. Ã‚Â Kata kunci : Denitrification, nitrate, autotrophic bacteria, elemental sulfur, pH.